Photoadaptation to the polar night by phytoplankton in a permanently ice‐covered Antarctic lake. (23rd May 2015) - Morgan‐Kiss, R. M.; Lizotte, M. P.; Kong, W.; Priscu, J. C.
Abstract: Photosynthetic microorganisms are a primary source of new organic carbon production in polar ecosystems. Despite their importance, relatively little is known about how they adapt to the bimodal solar cycles that exist at high latitudes. To understand how phytoplankton adapt to the extreme seasonal change in photoperiod, we transplanted cultures of a well‐studied laboratory model for photosynthetic cold adaptation, Chlamydomonas raudensis UWO241, back to the water column of Lake Bonney (McMurdo Dry Valleys, Antarctica) at the depth from which it was originally cultured. The organism was suspended at this depth in dialysis tubing to allow the microalga to respond to the in situ light, temperature and dissolved ions. We then integrated in situ biological and chemical measurements with environmental molecular analyses and compared the responses of transplanted C. raudensis cultures with the natural phytoplankton community over the 6‐week transition from Antarctic summer (24‐h daylight) to polar night (24‐h darkness). As solar radiation declined, natural communities exhibited a cessation of inorganic carbon fixation which was accompanied by a downregulation of expression of genes encoding for essential carbon fixation and photochemistry proteins. Transplanted C. raudensis cultures matched natural community trends in the regulation of photochemistry and carbon fixation gene expression, and shifted photochemical function to a shade adapted state in response to the polar night transition. We present a conceptual model for seasonal shifts in microbial community energy and carbon acquisition which integrates past cultivation‐based studies in this model photopsychrophile with a body of recent work on adaptation of natural populations to polar night.